Assessment of the impact of accidents involving hazardous substances on Car Lazar military barracks in Kruševac - Rutić, Srđan Z.; Inđić, Dejan R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The paper analyzes the risk of accidents involving hazardous substances during road and rail traffic in the city of Kruševac. Critical points in road and rail transport in the city of Kruševac are defined, followed by an analysis of the possibility of accidents in the transport of dangerous goods as well as an assessment of their impact on Car Lazar military barracks in Kruševac. It was concluded that Car Lazar barracks in Kruševac are significantly threatened by a possibility of accidents with hazardous materials in road and rail transport; therefore, particular attention should be paid to the prevention from accidents involving hazardous substances. Introduction Risks of chemical contamination due to accidents with hazardous materials are diverse and possible to occur as events in the past few years have shown. In urban areas, there are frequent breakdowns in stationary and mobile facilities (in production systems, warehouses, storage tanks, pipelines and conveyor belts). Harmful and hazardous substances can be poured into the environment, often suddenly and without control. By transporting highly toxic substances from one location to another, transport vehicles become active participants in traffic. Failure to comply with traffic regulations, especially in road transport, can often cause large-scale chemical accidents although all other measures related to proper handling and storage of hazardous substances in the vehicle are complied with. One of the factors comprised in the methodology of risk management is a three-phase analysis of the risk of accidents: - first phase - identification of hazards, - second phase - analysis of the consequences, and - third phase - risk assessment. The first phase deals with the collection of all data on dangerous activities and hazardous materials necessary for the impact analysis and risk assessment. The ultimate goal is to determine the types of potential contaminants and the type and properties of chemical substances that are transported. A starting point must be a collection of data on companies and other subjects engaged in the production, processing, storage and transportation of hazardous materials, as well as information about the type and amount of these substances. All hazardous materials are defined in the Regulations, in the list of hazardous substances. Risk assessment is done when hazardous substances that can cause chemical accidents are present in quantities equal to or greater than those specified in the list of hazardous substances (Article 4, Regulations on the methodology for risk assessment of chemical accidents and environmental pollution, Official Gazette of RS No. 60/94, Belgrade, 1994). A registry of potential hazardous sources is then created. Each substance from the registry has its properties determined. This data is important because of protection types, decontamination methods, methods for measuring affected areas, etc. In the second phase, during preparation for the analysis, a team of professionals of different specialties is formed. A display of possible developments is obtained by modeling the effects, which leads to modelling a possible extent of accidents and their consequences for lives and health of people and the environment. Modeling is a complex process, performed by using different models of effects: ideal, real, two-phase or combined ones. Their application helps in calculating the effects of the maximum amount of hazardous substances simultaneously released during an accident. The third phase is risk assessment. During transportation of highly toxic substances, it is extremely important to estimate a position of potential sources of danger. The parts of risk assessment are: - data on transport communications, - distance of the communications from facilities, - azimuth, - sectors with the highest probability of an accident, - relative altitude difference, - natural and artificial barriers between hazard sources and vulnerable facilities. Military facilities in Kruševac are at unfavorable locations (notably Car Lazar barracks), because they are in the city center and are likely to be put at risk in case of a chemical accident in the city. All critical points in road and rail transport are equally probable and the possibility of an accident at one of them is the same. Accidents can happen anywhere, but since these are the points with the largest number of traffic accidents during everyday traffic, chemical accidents are most likely to occur at these points. However, it can be concluded that the most dangerous points for endangering Car Lazar barracks are CT-4, CT-5 and CT-7 because of their proximity to the barracks. Whether vapor clouds are to reach the barracks depends on the amount of released material, the relative altitude difference, urban and transport infrastructure, and, primarily, on the distance of the accident from the barracks as well as the direction and strength of wind (since winds are unpredictable, it is not possible to know with certainty whether the barracks will be affected or not). It is safest to take adequate measures for the protection and evacuation (if necessary) immediately upon notification, regardless of the distance to the accident point, with the aim of saving human lives, thus avoiding any consequences and possible loss of manpower. Protection from chemical contamination is organized at the level of the garrison, on the basis of completed risk assessment. For the purpose of protection, there are specific, elaborated guidelines for the activities of on-duty bodies, teams, units and institutions as well as for the activities of commands dealing with the protection of personnel, food, water, weapons, equipment and facilities. The protection fundamentals comprise protective equipment and protective properties of buildings and equipment of units. In accordance with the assessment and a hazard level, facilities are adapted to protect people and goods (air-tight sealing, coverage, etc.). The protection of NBC units and others engaged in immediately affected regions is also provided by protective equipment for special purposes (protective overalls, isolating equipment, spare and industrial strainers). The organization of protection is a priority task for all safety personnel and it is carried out in order to save lives and health of people and create favourable conditions for life and operation of units. Conclusion When all the specific details of accidents during production and transport of highly toxic substances are taken into account, it can be concluded that the organization of the answer to this kind of accidents is an extremely complicated and complex activity that requires fully qualified personnel, trained to effectively respond to accidents with hazardous materials. It can also be concluded that the organization of risk management in this kind of emergency situation is an extremely complicated and complex activity, requiring a systematic and multidisciplinary approach. The ultimate goal of all efforts in addressing this problem is to reduce, ie. to minimize risk in all phases of accident management. The existence of critical points in road and rail transport in Kruševac is directly related to a possibility of accidents involving hazardous substances. The Army of Serbia has a significant place and role in preventing such accidents both in the military and the civilian sector. After taking into account all the elements of the assessment of potential accidents involving hazardous substances and their mutual influence, one can draw a conclusion which is a basis for planning and organising Army units and institutions in case of accidents involving hazardous substances. Car Lazar barracks in Kruševac are at high risk of accidents with hazardous materials in road and rail transport; therefore, a particular attention should be paid to the prevention from accidents involving hazardous substances.